1996
DOI: 10.1017/s0033291700035303
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological impairments in unipolar depression: the influence of perceived failure on subsequent performance

Abstract: SynopsisThe CANTAB battery of neuropsychological tests was used to compare the performance of 28 patients with unipolar depression with that of 22 age and IQ matched controls. The patients were impaired on almost all tests studied with deficits in pattern and spatial recognition memory, matching to sample, spatial span, spatial working memory and planning. Most of the patients showed at least some impairment and deficits were seen across cognitive domains. An important finding was the detrimental effect of fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
334
8
10

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(391 citation statements)
references
References 45 publications
(62 reference statements)
39
334
8
10
Order By: Relevance
“…Indeed, Rogers et al (2003) recently reported that ATD impaired the ability to discriminate between large and small rewards. Diminished behavioral sensitivity to cues signaling reward and enhanced behavioral sensitivity to cues signaling punishment may parallel previous findings, indicating that depression, associated with diminished 5-HT function, is characterized by under-sensitivity to reward (Henriques et al, 1994) and over-sensitivity to negative feedback (Elliott et al, 1996(Elliott et al, , 1997Murphy et al, 2002Murphy et al, , 2003. ATD did not affect SSRT, a measure of prepotent response inhibition.…”
Section: Discussionsupporting
confidence: 72%
“…Indeed, Rogers et al (2003) recently reported that ATD impaired the ability to discriminate between large and small rewards. Diminished behavioral sensitivity to cues signaling reward and enhanced behavioral sensitivity to cues signaling punishment may parallel previous findings, indicating that depression, associated with diminished 5-HT function, is characterized by under-sensitivity to reward (Henriques et al, 1994) and over-sensitivity to negative feedback (Elliott et al, 1996(Elliott et al, , 1997Murphy et al, 2002Murphy et al, , 2003. ATD did not affect SSRT, a measure of prepotent response inhibition.…”
Section: Discussionsupporting
confidence: 72%
“…This was ascertained by the observations of nursing and medical staff and from patients' own accounts. Patients received a comprehensive battery of neuropsychological measures and clinical ratings at 8 a.m. and 8 p.m., in a balanced design, such that half received their first battery of measures at 8 a.m., the other half at 8 p.m. Only results for performance on the simultaneous and delayed matching to sample are reported here, since previous work suggests this measure shows the largest abnormality in the response to perceived failure (Elliott et al 1996(Elliott et al , 1997. Patients and controls were also assessed prior to both psychometric testing sessions on parallel versions of the BFS (von Zerssen et al 1974), an adjective checklist sensitive to changes in current fatigue and depression.…”
Section: Studymentioning
confidence: 99%
“…It is also suggested that this method of calculation controls for the overall error rate. The assumption is that, if the errors are independent of each other, an increase in the overall failure rate will lead to a proportional increase in the number of errors following errors, and so not have an effect on the overall conditional probability (Elliott et al 1996).…”
Section: Conditional Probability Analysis and The ' Runs ' Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Many neuropsychological studies document working memory deficits in individuals with MDD. [13][14][15][16][17][18] MDD patients perform poorly on the n-back task, a working memory task, compared to healthy controls, and their performance on the n-back task is inversely correlated with the severity of their depression. 19 The n-back task performance of both depressed and remitted elderly MDD patients is significantly inferior to that of control subjects, suggesting that the impairment of working memory is a trait marker of geriatric depression.…”
Section: Introductionmentioning
confidence: 99%